2019
DOI: 10.2478/bjreecm-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Construction Cost Estimate in Yemen by Artificial Neural Network

Abstract: The construction industry in Yemen is currently facing challenges associated with rapid development of technology; thus, cost estimation is considered a key factor that should align with this technological advancement. The main problem in the area of preliminary estimate in Yemen is how to make estimate accurately. The aim of this study is to analyse a modern method of preliminary cost estimation in Yemen to prove its efficiency over the traditional method. Therefore, a wide range of literature sources regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…In another emerging economy, this time that of Yemen, a study was carried out to provide a cost prediction tool based on ANN models by Hakami and Hassan [42], based on historical data from 136 buildings constructed from 2011 to 2015. They included 17 independent variables to be implemented in their model to produce a preliminary total construction cost estimate.…”
Section: Application Of Anns To Cost Estimation In the Particular Fie...mentioning
confidence: 99%
“…In another emerging economy, this time that of Yemen, a study was carried out to provide a cost prediction tool based on ANN models by Hakami and Hassan [42], based on historical data from 136 buildings constructed from 2011 to 2015. They included 17 independent variables to be implemented in their model to produce a preliminary total construction cost estimate.…”
Section: Application Of Anns To Cost Estimation In the Particular Fie...mentioning
confidence: 99%
“…They choose 3 hidden layers model with 20 projects data. Moreover, in Yemen, Hakami and Hassan (2019) studied preliminary construction cost estimation by using ANN with one hidden layer and 136 different projects. As a result of their study, they found the MAPE value as 0.14%.…”
Section: Previous Studies On Cost Estimationmentioning
confidence: 99%